Implementation of Technical Aspects of Strengthening Existing Structural Columns Using Jacketing Fiber Reinforced Polymer (FRP) - Annisa' Carina; Blima Oktaviastuti; Heru Setiyo Cahyono (Universitas Tribhuwana Tunggadewi Malang, 2025)
Columns are vertical structural elements in construction planning and implementation, which play a crucial role in distributing loads from the superstructure to the foundation. Therefore, columns must meet the strength and safety standards stipulated in technical regulations such as SNI 2847:2019 and ACI 440.2R-17. However, in reality, structural columns are often found to have strengths that are less than required. The need to strengthen existing structural columns generally arises due to several reasons, including revisions to building functions that cause additional loads, aging buildings that begin to exhibit a decrease in structural capacity, or discrepancies between actual conditions and the initial planning design. This research was conducted on eight columns of the first floor structure of the JIIPE Tower construction project. The columns that were the object of the research are part of the main structure of a multi-story building planned as the JIIPE Tower building. Based on the results of calculations using SAP2000 for longitudinal and transverse reinforcement against the column force and geometry requirements, it is evident that the columns meet the requirements for the shortest side and the requirements for the cross-sectional dimension ratio; however, they do not meet the Axial Force Requirements. The study results show that the proper use of FRP can be an efficient and effective reinforcement method in increasing column capacity.